Efficacy of fosinopril and amlodipine in pediatric primary hypertension: a single-center observational study - Wang, Hui; Shi, Lin; Lin, Yao; Wang, Yuting; Niu, Wenquan; Li, Yaqi (Frontiers in Pediatrics, 2023)
Objective Fosinopril and amlodipine are commonly prescribed as first-line pharmacotherapeutic agents for pediatric hypertension, but there is a lack of comparative studies regarding the efficacy of these two drugs. We aimed to evaluate and compare the efficacy of fosinopril and amlodipine monotherapy in pediatric primary hypertension. Methods This was a single-center, bidirectional observational study. A total of 175 children and adolescents with primary hypertension receiving antihypertensive monotherapy from July 2020 to February 2023 were enrolled. According to antihypertensive drugs, they were divided into the fosinopril group (n = 96) and the amlodipine group (n = 79). Subgroup analysis was performed to compare the efficacy of the two groups in terms of blood pressure (BP) control rates and reductions following a 4-week treatment. Results After 4 weeks of treatment, both groups achieved significant reductions in systolic BP (SBP) and diastolic BP (DBP) by more than 18 mmHg and 6 mmHg, respectively, with BP control rates of 61.5% in the fosinopril group and 59.5% in the amlodipine group, revealing no significant differences in the antihypertensive efficacy between the two groups except for DBP control rate (FDR adjusted P > 0.05). Further subsequent subgroup analyses revealed that the reductions in SBP and DBP in the fosinopril group were significantly greater than those in the amlodipine group in patients of females and hypo-HDL-cholesterolemia (FDR adjusted P < 0.05), and there was a trend of difference, although not significant, in patients with central obesity and insulin resistance (IR) (FDR adjusted 0.05 < P ≤ 0.1). However, there were no significant differences in treatment efficacy in patients without these characteristics. Furthermore, hypertriglyceridemia did not exhibit a significant association with the difference in treatment efficacy between the two medications (FDR adjusted P > 0.05). Conclusions Fosinopril and amlodipine monotherapy were both effective in pediatric primary hypertension during a short-term follow-up. Fosinopril may be particularly effective in reducing BP in hypertensive patients of females, central obesity, IR, and hypo-HDL-cholesterolemia. These findings indicate that optimizing antihypertensive medication selection based on the individualized characteristics of children with hypertension may improve the efficacy of antihypertensive treatment.